Penerapan Model Pembelajaran Take and Give Untuk Meningkatkan Hasil Belajar PKn - Suratmin Suratmin (JURNAL GLOBAL EDUKASI, 2017)
Abstract: The purpose of this classroom action research is to know the improvement of Civic learning outcomes through the application of take and give learning model. Subjects in this study were students of grade IV SDN 014679 Bangun Sari kec. Faithful Promise TP. 2016/2017. Based on the results of research can be drawn conclusions based on the results and data proved that the implementation of learning model Take and Give can improve student learning outcomes. In the first cycle obtained an average score of 69.42 with classical learning completeness 69.66%. In the second cycle there was an average increase of 87.5 with classical learning completeness of 88.41%. Keyword: take and give Abstrak: Tujuan penelitian tindakan kelas ini adalah untuk mengetahui peningkatan hasil belajar PKn melalui penerapan model pembelajaran take and give. Subjek dalam penelitian ini adalah siswa kelas IV SDN 014679 Bangun Sari kec. Setia Janji TP. 2016/2017. Berdasarkan hasil penelitian dapat diambil kesimpulan berdasarkan hasil dan data terbukti bahwa penerapan model pembelajaran Take and Give dapat meningkatkan hasil belajar siswa. Pada siklus I diperoleh nilai rata-rata sebesar 69,42 dengan ketuntasan belajar klasikal 69,66%. Pada siklus II terjadi peningkatan nilai rata-rata sebesar 87,5 dengan ketuntasan belajar klasikal sebesar 88,41%. Kata kunci: take and give